The Impact of Working Capital, Leverage and Liquidity on Profitability: Evidence from Manufacturing Firms in Pakistan - Mubashir Zaman; Sana Nazakat; Farhan Ahmad; Moeen Abbas (Indus Journal of Social Sciences, 2025)
The research aimed to assess the impact of working capital turnover, liquidity, and leverage on the profitability of the firms. This study used secondary data from the financial statements of 25 manufacturing firms listed on the Pakistan Stock Exchange (PSX) 100 index. The data period consists of 2014 to 2024, and the total number of samples obtained was 275. This study employed causal associative research. Therefore, constructed the panel data technique approach. The regression analytical approach is utilized for hypothesis testing. The Shapiro-Wilk test results demonstrate that all variable distributions are normal. Regression analysis findings show that working capital turnover shows no significant impact on the profitability of the firms. Whereas leverage shows a negative impact on profitability, and liquidity shows a positive significant impact on the profitability of the firms.